Timing of Pubertal Maturation in Girls An Integrated Life History Approach. (Articles ). - Ellis, Bruce J.
Life history theory provides a metatheoretical framework for the study of pubertal timing from an evolutionary -developmental perspective. The current article reviews 5 middle-level theories-energetics theory, stress -suppression theory, psychosocial acceleration theory, paternal investment theory, and child development theory-each of which applies the basic assumptions of life history theory to the question of environmental influences on timing of puberty in girls. these theories converge in their conceptualization of pubertal timing as responsive to ecological conditions but diverge in their conceptualization of (a) the nature extent and direction of environmental influences, and (b) the effects of pubertal timing on other reproductive variables . Competing hypothesis derived from the 5 perspective are evaluated. An extention of W. T. Boyce B. J. Ellis's (in press) theory of stress on timing of pubertal development. This review highlights the multiciplity of (often unrecognized) perspective guiding research, raises challenges to virtually all of these, and presents an alternative framework in an effort to move research forward in this arena of multidisciplinary inquiry. -- (from the author)